Evolution-Driven Attenuation of Alphaviruses Highlights Key Glycoprotein Determinants Regulating Viral Infectivity and Dissemination - Maria G. Noval; Bruno A. Rodriguez-Rodriguez; Margarita V. Rangel; Kenneth A. Stapleford (Cell Reports, 2019)
Summary: Understanding the fundamental mechanisms of arbovirus transmission and pathogenesis is essential to develop strategies for treatment and prevention. We previously took an in vivo evolution-based approach and identified the chikungunya virus E1 glycoprotein residue 80 to play a critical role in viral transmission and pathogenesis. In this study, we address the genetic conservation and function of position 80 and demonstrate that this residue is a key determinant in alphavirus infectivity and dissemination through modulation of viral fusion and cholesterol dependence. In addition, in studying the evolution of position 80, we identified a network of glycoprotein residues, including epidemic determinants, that regulate virus dissemination and infectivity. These studies underscore the importance of taking evolution-based approaches to not only identify key viral determinants driving arbovirus transmission and pathogenesis but also to uncover fundamental aspects of arbovirus biology. : Noval et al. take an evolution-based approach to understand chikungunya virus (CHIKV) E1 glycoprotein function and highlight position 80 as a key determinant regulating CHIKV infectivity and spread in vivo, functioning through epistatic interactions with other glycoprotein residues to coordinate cholesterol-dependent entry. Keywords: alphaviruses, chikungunya virus, E1 glycoprotein, cholesterol dependence, fusion, viral dissemination